Bibliometric Analysis of Global Policy: A Scholarly Journal of Durham University, UK - Hussain, Abid; ul-Haq, Sayyed Ihtisham (Access: An International Journal of Nepal Library Association, 2024)
This study seeks to evaluate the corpus of work published in the peer-reviewed Journal Global Policy, associated with Durham University, UK. Employing bibliometric techniques, the research analyzes publications from 2010 to 2021. Bibliometric analysis encompasses various facets of scholarly work, including authorship patterns, leading institutions, and the geographical distribution of contributing authors. The study identifies that 159 authors produced a total of 1139 papers across 12 volumes and 75 issues within the specified timeframe. The findings highlight that authors from the United States were the most prolific, contributing 306 articles (21.11%) during this period. Among institutions, the London School of Economics and Political Science emerged as the most active, with 74 articles published. This research represents the inaugural bibliometric analysis of Global Policy, with no prior studies applying such techniques to this Journal. The scope of this study is confined to publications from 2010 to 2021. The findings offer valuable insights for stakeholders, editors, and researchers contributing to the Journal and will aid librarians and research scholars in planning future bibliometric analyses on related subjects.